Miteinander sprechen - verantwortlich, kompetent, reflektiert - Voigt-Zimmermann, Susanne (Schriften zur Sprechwissenschaft und Phonetik, 2021)
Speech science has a history of over 120 years. In addition to the self-image of the discipline, this book focuses on everything that makes the subject so attractive: With its vital research and teaching subject, speaking and people talking to each other, it is both application-oriented and up-to-date. This explains the continuing high level of interest among students, research partners, and practical professional fields in education, art, media, counseling, therapy, and prevention. With study locations in Halle, Jena and Marburg, Speech Science is represented throughout Germany. As an interdisciplinary research and working subject with links to linguistics, medicine, pedagogy, psychology, politics and sociology, among others, there are also diverse collaborations in research, teaching and practice. This volume offers surprising insights into the diversity of speech science - from its history to the present to an outlook on what will be possible in the future. Susanne Voigt-Zimmermann holds a degree in speech science. After scientific, speech-educational, and clinical-therapeutic activities at the universities of Jena, Heidelberg, and Magdeburg, she has been a professor of speech science at the Department of Speech Science and Phonetics at Martin Luther University Halle-Wittenberg since 2017.